2020
DOI: 10.1101/2020.02.10.941252
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acetylation of isoniazid - a novel mechanism of isoniazid resistance inMycobacterium tuberculosis

Abstract: Isoniazid (INH)

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…One example would be the Rv2170 gene, which in our study increases sensitivity to isoniazid and has been shown to confer resistance when its expression is increased because it encodes an acetyl-transferase that inactivates isoniazid. 25 Although we could not find insertion mutants for target isoniazid gene inhA due to its essentiality, non-essential genes in the mycolic acids biosynthesis pathway were functionally more associated with resistance than the rest of the genome, showing that the target pathway can be identified even when the target gene itself is essential. Functional genomics also pointed to redox metabolism as a resistance mechanism for isoniazid, confirming the usefulness of this technique in highlighting resistance determinants not directly tied to the drug’s mode of action and in helping complete the resistance mutations catalog.…”
Section: Discussionmentioning
confidence: 80%
“…One example would be the Rv2170 gene, which in our study increases sensitivity to isoniazid and has been shown to confer resistance when its expression is increased because it encodes an acetyl-transferase that inactivates isoniazid. 25 Although we could not find insertion mutants for target isoniazid gene inhA due to its essentiality, non-essential genes in the mycolic acids biosynthesis pathway were functionally more associated with resistance than the rest of the genome, showing that the target pathway can be identified even when the target gene itself is essential. Functional genomics also pointed to redox metabolism as a resistance mechanism for isoniazid, confirming the usefulness of this technique in highlighting resistance determinants not directly tied to the drug’s mode of action and in helping complete the resistance mutations catalog.…”
Section: Discussionmentioning
confidence: 80%
“…Thus, sensitivity-increasing genes can also act as resistance determinants depending on how mutations affect the protein or its expression levels. One example would be the Rv2170 gene, which in our study increases sensitivity to isoniazid and has been shown to confer resistance when its expression is increased because it encodes an acetyl-transferase that inactivates isoniazid [78]. Although we could not find insertion mutants for target isoniazid gene inhA due to its essentiality, non-essential genes in the mycolic acids biosynthesis pathway were functionally more associated with resistance than the rest of the genome, showing that the target pathway can be identified even when the target gene itself is essential.…”
Section: Discussionmentioning
confidence: 98%